Exciton Formation at Solid-Solid Interfaces: a systematic experimental and ab initio Study on compressed MgO Nanopowders - Sternig, Andreas; Koller, David; Siedl, Nicolas; Diwald, Oliver; Mckenna, Keith (Journal of Physical Chemistry C, 2012)
An important and so far neglected class of structural elements affecting the overall properties of metal oxide nanopowders are interfaces between individual nanocrystals. In this work we show experimentally that these defects inside a powder of compressed MgO nanocubes are subject to photoexcitation in the UV light range. In particular, we identify a so far unobserved photoluminescence emission process at 2.5 eV. First principles calculations of the optical properties of nanocrystal interfaces provide plausible candidates for both light absorbing and emitting sites which involve different types of interface features. It was found that edge dislocations that arise from interfaces between nanocube edges and terraces induce a significant electrostatic perturbation of the interfacial electronic states. This leads to exciton generation and luminescence at even lower energies than those related to corners and edges of MgO nanocubes
EAM Import::2019-03-14